2012
DOI: 10.4103/0974-7796.91618
|View full text |Cite
|
Sign up to set email alerts
|

Management of nephrolithiasis in autosomal dominant polycystic kidney disease - A single center experience

Abstract: Purpose:To evaluate available options for the management of nephrolithiasis in patients with autosomal dominant polycystic kidney disease (ADPKD).Materials and Methods:Case files of all the patients with ADPKD treated in our hospital in the last 18 years were evaluated. Their demographic details, clinical presentations, investigations, treatments, and outcomes were critically analyzed.Results:There were a total of 19 patients (23 renal units) with nephrolithiasis among 452 consecutive cases of ADPKD. Male-to-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 8 publications
(15 reference statements)
0
27
0
Order By: Relevance
“…There are few papers and case reports on the PNL in ADPKD with limited number of patients and experience. The PNL in ADPKD create some difficulty such as distorted pelvicaliceal system leading to difficult puncture and dilatation, cyst puncture, cyst bleeding, cyst infection and associated parenchymal calcifications misleading to presence of stones under the fluoroscopy [1,2,4,5,6,7,8]. Umbreit et al [9] found that PNL to be safe and effective in ADPKD with large stone burden despite the increased operative complexity, need of multiple punctures and repeat nephroscopy.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…There are few papers and case reports on the PNL in ADPKD with limited number of patients and experience. The PNL in ADPKD create some difficulty such as distorted pelvicaliceal system leading to difficult puncture and dilatation, cyst puncture, cyst bleeding, cyst infection and associated parenchymal calcifications misleading to presence of stones under the fluoroscopy [1,2,4,5,6,7,8]. Umbreit et al [9] found that PNL to be safe and effective in ADPKD with large stone burden despite the increased operative complexity, need of multiple punctures and repeat nephroscopy.…”
Section: Discussionmentioning
confidence: 99%
“…The important complications which occur due to this disease are the hypertension, renal failure, nephrolithiasis, hemorrhage and infections [1]. The nephrolithiasis occurs in about 8-36% of the patients which increases the morbidity and further accelerates the onset of renal failure [2].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although extracorporeal shock wave lithotripsy is least invasive and its stone-free rate is similar to those achieved by percutaneous nephrolithotomy (PCNL) and ureteroscopy, its limitations lie in long-term complications like renal dysfunction and hypertension, which make its efficacy questionable [7]. PCNL has been reported for treatment of very few cases recently and its effect is acceptable [8,9]. Nevertheless, the deformed anatomy and the impairment of renal function of ADPKD with renal calculi still make minimally invasive PCNL a very challenging procedure.…”
Section: Introductionmentioning
confidence: 99%